2006
DOI: 10.1029/2005jb003732
|View full text |Cite
|
Sign up to set email alerts
|

Mantle melting as a function of water content beneath back‐arc basins

Abstract: [1] Subduction zone magmas are characterized by high concentrations of H 2 O, presumably derived from the subducted plate and ultimately responsible for melting at this tectonic setting. Previous studies of the role of water during mantle melting beneath back-arc basins found positive correlations between the H 2 O concentration of the mantle (H 2 O o ) and the extent of melting (F), in contrast to the negative correlations observed at mid-ocean ridges. Here we examine data compiled from six back-arc basins an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
325
2
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 277 publications
(348 citation statements)
references
References 110 publications
18
325
2
3
Order By: Relevance
“…Samples with MgO b 8 wt.% were given the Fe 8.0 and Na 8.0 expressions of Klein and Langmuir (1987) to correct the MgO, FeO and Na 2 O concentrations. Kelley et al (2006) showed that most melts with MgO b 8.5 wt.% are still on the olivine + plagioclase cotectic and adding olivine at this point would lead to a false high FeO content. To further remove the effect of plagioclase, expressions of Kelley et al (2006) were employed to make an additional fractionation correction to 8.5 wt.% MgO.…”
Section: Primary Magma and Melting Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Samples with MgO b 8 wt.% were given the Fe 8.0 and Na 8.0 expressions of Klein and Langmuir (1987) to correct the MgO, FeO and Na 2 O concentrations. Kelley et al (2006) showed that most melts with MgO b 8.5 wt.% are still on the olivine + plagioclase cotectic and adding olivine at this point would lead to a false high FeO content. To further remove the effect of plagioclase, expressions of Kelley et al (2006) were employed to make an additional fractionation correction to 8.5 wt.% MgO.…”
Section: Primary Magma and Melting Conditionsmentioning
confidence: 99%
“…Kelley et al (2006) showed that most melts with MgO b 8.5 wt.% are still on the olivine + plagioclase cotectic and adding olivine at this point would lead to a false high FeO content. To further remove the effect of plagioclase, expressions of Kelley et al (2006) were employed to make an additional fractionation correction to 8.5 wt.% MgO. Samples with MgO between 8.0 and 8.5 wt.% were corrected to 8.5 wt.% MgO only along this linear olivine + plagioclase cotectic (Kelley et al, 2006).…”
Section: Primary Magma and Melting Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…(b) A plot of TiO 2 /Y ratios versus Na 2 O contents for Fina Nagu volcanic chain lavas and MalaguanaGadao ridge lavas. The black line shows the trajectory of a melt produced by bath melting a normal MORB composition mantle from Kelley et al [2006]. Arrows show the general effects of increasing melt fraction and increasing source depletion on the composition of melts.…”
Section: Dissolved H 2 O and Comentioning
confidence: 99%
“…The degrees of melting of the DMM were estimated for the lower-K primary magma based on the distribution of Ti between the source mantle and melt following the method of Kelley et al (2006). Using the bulk distribution coefficient for Ti of 0.04 and a TiO 2 content of the DMM of 0.133 wt.% (Salters and Stracke 2004) Fig.…”
Section: Conditions Of Magma Generationmentioning
confidence: 99%